Technologies For Processing Grape Antioxidative Protection With Antioxidant Activity Of Wines. (Texas Journal of Agriculture and Biological Sciences, 2023)
In the technological chain of wine preparation, oxidative processes begin immediately after the grape harvest, which, in accordance with the recommendations must be protected with sulfur dioxide (SO2). Studying the state of the antioxidant protection system during grape processing and when obtaining wine materials is of particular interest and will make it possible to regulate the degree of protection of the must and wine materials from oxidative stress, which is especially important when processing grapes into slightly oxidized table wines. Using the redox potential value, you can characterize the degree of oxidation of wine and control the production of various types of wines